2013
DOI: 10.1136/bjophthalmol-2012-302292
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab therapy for refractory uveitis: results of a multicentre, open-label, prospective trial

Abstract: Adalimumab was safe and effective in 68% of refractory uveitis patients 10 weeks after study enrolment, and maintained in 39% after 1 year. Ongoing study is required to determine the place of adalimumab and other TNF blockers in the treatment of uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 32 publications
4
77
1
8
Order By: Relevance
“…24 In another non-comparative open-label prospective study of 31 patients with refractory uveitis, 68% of patients were clinical responders at 10 weeks, with sustained response at 50 weeks seen in 39% of the patients. 25 A multicenter prospective study of 131 patients with a mean age of 27 years also demonstrated that adalimumab therapy significantly improved anterior chamber and vitreous inflammation with the ability to taper CS. 14 The French uveitis network recently published a multicenter observational study of 160 patients with refractory uveitis treated with anti-TNFα (infliximab and adalimumab) agents.…”
Section: Discussionmentioning
confidence: 96%
“…24 In another non-comparative open-label prospective study of 31 patients with refractory uveitis, 68% of patients were clinical responders at 10 weeks, with sustained response at 50 weeks seen in 39% of the patients. 25 A multicenter prospective study of 131 patients with a mean age of 27 years also demonstrated that adalimumab therapy significantly improved anterior chamber and vitreous inflammation with the ability to taper CS. 14 The French uveitis network recently published a multicenter observational study of 160 patients with refractory uveitis treated with anti-TNFα (infliximab and adalimumab) agents.…”
Section: Discussionmentioning
confidence: 96%
“…21 In another non-comparative open-label prospective study of 31 participants with refractory uveitis, 68% of participants were clinical responders at 10 weeks, and sustained response at 50 weeks was seen in 39% of the participants. 22 The French uveitis network recently published a multicenter study of 160 participants with refractory uveitis treated with anti-TNFα (infliximab and adalimumab) agents. The participants had an overall response rate of 93% at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Case series, observational studies, and open-label prospective clinical trials show that adalimumab can be efficacious for uveitis refractory to conventional immunosuppressive therapy in the context of scleritis, JIA-associated anterior uveitis, HLA-B27-associated anterior uveitis, tubulointerstitial nephritis and uveitis syndrome (TINU), ocular sarcoidosis, birdshot retinochoroidopathy, VKH, and idiopathic uveitis (Simonini et al 2014;Ragam et al 2014;Díaz-Llopis et al 2012;Restrepo and Molina 2010;Suhler et al 2013). An open-label study examining the efficacy of adalimumab for noninfectious uveitis refractory to at least one standard immunosuppressive medication showed a 68% response rate at 10 weeks and a 39% response rate at 50 weeks (Suhler et al 2013).…”
Section: Tnfa Antagonistsmentioning
confidence: 99%
“…An open-label study examining the efficacy of adalimumab for noninfectious uveitis refractory to at least one standard immunosuppressive medication showed a 68% response rate at 10 weeks and a 39% response rate at 50 weeks (Suhler et al 2013). …”
Section: Tnfa Antagonistsmentioning
confidence: 99%